Short-term program of aerobic training prescribed using critical velocity is effective to improve metabolic profile in postmenopausal women - Diniz, T. A. [UNESP]; Fortaleza, A. C.S. [UNESP]; Rossi, F. E. [UNESP]; Neves, L. M. [UNESP]; Campos, E. Z. [UNESP]; Freitas Junior, I. F. [UNESP] (Elsevier, 2016)
Purpose: The aim of this study was to verify the effectiveness of an eight-week aerobic training prescribed by the critical velocity on metabolic profile. Methods: The participants were divided into two groups: Aerobic Training (AT [n = 10]) and Control group (CG [n = 9]). Aerobic intensity was prescribed using critical velocity and the women exercised during eight weeks. The trunk body fat (TBF), body fat (BF) and fat-free mass were estimated using DXA. The total cholesterol (TC), low-density lipoprotein (LDL-c), high-density lipoprotein (HDL-c), triacylglycerol and glucose were analyzed in a particular laboratory. Results: After eight weeks, there were statistically significant differences between AT and CG in TBF (CG = 4.27 ± 5.10 vs. AT = -3.13 ± 4.65; P = 0.006), BF in kg (CG = 2.79 ± 5.91 vs. AT = -2.75 ± 3.01; P = 0.015) and percentage (CG = 1.83 ± 3.67 vs. AT = -2.40 ± 2.67; P = 0.010), LDL-c levels (CG = 10.95 ± 23.63 vs. AT = -11.96 ± 22.00; P = 0.045) and a tendency in TC (GC = 9.00 ± 15.59 vs. AT = -6.67 ± 16.43; P = 0.052). Conclusion: In summary, the present study suggests that even a short-term of aerobic training, prescribed using critical velocity, is effective in decreasing whole body fat, central adiposity and low-density lipoprotein-cholesterol in postmenopausal women.
Keywords: Endurance training; Lipoproteins; Menopausal women; Obesity